STRATEGI PENINGKATAN PANGSA PASAR ANGKUTAN UMUM DI KOTA SURAKARTA - Arif Budiarto; Ade Sjafruddin; Idwan Santoso; Harun Alrasyid Sorah Lubis (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2010)
An important problem in urban areas is traffic congestion that occurs on the road network during the day. One cause of this problem is the high number of private car usage with low occupancy levels while public transport services are under-utilized, although the use of public transport is more efficient than that of private cars. Therefore, efforts to increase public transport use are needed to reduce transportation problems, such as traffic congestion. Mode choice is one important step in transportation modeling because this stage provides information necessary to evaluate the condition of the transportation network, including traffic congestion in the network. This model aims to determine the individual attributes and modes, which influence in selecting a mode among available modes, using the utility function parameters. Sensitivity of mode choice can be seen through the sign and magnitude of the parameters contained in this model. In this study, a simulation was conducted with a purpose to increase the market share of public transport in the City of Surakarta.Keywords: mode choice, utility function, public transport